Degradation kinetics of medium chain length Polyhydroxyalkanoate degrading enzyme: a quartz crystal microbalance study - Millan, Fabien; Hanik, Nils (Frontiers in Bioengineering and Biotechnology, 2023)
This study investigates the enzymatic degradation processes of different classes of polyhydroxyalkanoates (PHAs), a group of biopolymers naturally synthesized by various microorganisms. Medium chain length PHAs (mcl-PHAs) are distinguished biopolymers due to their biodegradability and diverse material properties. A detailed understanding of their enzymatic degradation kinetics supports the optimization of their industrial and biomedical applications. Using quartz crystal microbalance measurements as a valuable tool for accurate real-time monitoring of the enzymatic degradation process, the research provides detailed kinetic data, describing the interaction between enzymes and substrates during the enzymatic degradation process. Thin films of poly-3-hydroxybutyrate (PHB) and polyhydroxyoctanoate copolymer (PHO), containing molar fractions of about 84% 3-hydroxyoctanoate and 16% 3-hydroxyhexanoate, were exposed to scl-depolymerases from Pseudomonas lemoignei LMG 2207 and recombinant mcl-depolymerases from produced in Echerichia coli DH5α harboring the plasmid pMAD8, respectively. Analyses based on a heterogeneous kinetic model for the polymer degradation indicated a six-fold stronger adsorption equilibrium constant of mcl-depolymerases to PHO. Conversely, the degradation rate constant was approximately twice as high for scl-depolymerases acting on PHB. Finally, the study highlights the differences in enzyme-substrate interactions and degradation mechanisms between the investigated scl- and mcl-PHAs.